PENGARUH KOMUNIKASI ITERNAL TERHADAP MOTIVASI KERJA PEGAWAI PADA KANTOR CAMAT ULUSUSUA KABUPATEN NIAS SELATAN - Wedirman Halawa (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The Ulususua District Office, South Nias Regency, was the setting for this study, which sought to ascertain how internal communication affected work motivation among employees. Qualitative causal research is the method of this study. to determine how internal communication affects employees' motivation to work. The participants in this study were all employees of the South Nias Regency's Ulususua sub-district office. There were 30 respondents in this study's sample. Partially test the hypothesis that Internal Communication is an independent variable with tcount 2.126 > ttable 1.701, then Ha is accepted and ho is rejected, indicating that the Internal Communication variable (X) influences the Employee Work Motivation variable (Y) at the Ulususua Sub-District Office. This leads the researchers to the conclusion that Internal Communication has a partial influence on Employee Work Motivation and that it is significant.